2011
DOI: 10.1080/0376835x.2011.570072
|View full text |Cite
|
Sign up to set email alerts
|

Creating job satisfaction in Africa: A case study from Mozambique

Abstract: How to set up successful multicultural human resource management programmes remains a contentious issue. This study examined variables that influenced job satisfaction in the workforce of a multinational company operating in Mozambique. It took a mixed methods approach and analysed case study data using a combination of content, thematic, descriptive and statistical techniques. The results indicate that the level of job satisfaction of these employees was comparable to that of employees in former Soviet Bloc c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Mueller et al, 2009;Noordin and Jusoff, 2010) or polycentric studies concerning what determines job satisfaction in various countries (e.g. Sartorius et al, 2011;Alas and Edwards, 2011), or they compared the level of job satisfaction among various diversity groups (e.g. Shore et al, 2009;Strydom and van Eeden, 2013).…”
Section: The Narrative Review 31 Methodsmentioning
confidence: 99%
“…Mueller et al, 2009;Noordin and Jusoff, 2010) or polycentric studies concerning what determines job satisfaction in various countries (e.g. Sartorius et al, 2011;Alas and Edwards, 2011), or they compared the level of job satisfaction among various diversity groups (e.g. Shore et al, 2009;Strydom and van Eeden, 2013).…”
Section: The Narrative Review 31 Methodsmentioning
confidence: 99%
“… Macedonia: impact of coping strategies and helpful work environment on job satisfaction (Sardzoska and Tang, 2012).  Mozambique: variables influencing job satisfaction in the workplace of a multinational company (Sartorius et al 2011).  Pakistan: impact of work-life balance on job satisfaction (Malik et al 2010).…”
mentioning
confidence: 99%
“…They analyzed nonpanel longitudinal data from the International Social Survey Program on Work Orientations across different countries for 1997 and 2005 and found that the respondents from different countries share similarities in terms of what satisfies them in their jobs, but emphasis placed on these factors vary for some countries. (2) Sartorius et al (2011) examined variables that influenced job satisfaction in the workplace of a multinational company operating in Mozambique and concluded that to be more successful 'foreign' management practice should be adapted to the local culture.…”
mentioning
confidence: 99%